Antimicrobial activity of a temporary sealant used in endodontic treatment: An in vitro study - Domingos, Helena Baruffaldi; Gonçalves, Lucio Souza; de Uzeda, Milton (European Journal of Dentistry, 2015)
Objective: The present study is aimed to evaluate the antimicrobial action of Coltosol® in direct contact with human saliva. Materials and Methods: Twelve different individuals were selected. Saliva samples were evaluated at four different time periods: Baseline 1 (T1-initial control), T2 (2 h), T4 (24 h after contact with a standardized sample of a coronary sealer) and baseline 2 (T3-fi nal control). Seeded plates were incubated at 37°C in a bacterial incubator for a period of 48–72 h. After the incubation period, the colony forming units were counted, and the results compared. Results: Differences were statistically significant. There was an inhibition of bacterial growth after the fi rst 2 h of contact and an increase in the number of bacteria after 24 h of direct contact between the material and the saliva. Coltosol® presented bacterial growth inhibition in direct contact with saliva. This inhibitory effect tended to decrease over time, as shown by the two periods when the material was in contact with different samples of saliva. Conclusions: The antimicrobial activity of the material is an important feature; however, other physical and chemical properties of the coronary temporary sealer should be considered.
Keywords: Antimicrobial; dental materials; saliva